Microfabricated substrates as a tool to study cell mechanotransduction - Le Digabel, Jimmy; Ghibaudo, Marion; Trichet, Léa; Richert, Alain; Ladoux, Benoit (Medical & Biological Engineering & Computing, 2010)
Mechanical cell-substrate interactions affect many cellular functions such as spreading, migration, and even differentiation. These interactions can be studied by incorporating micro- and nanotechnology-related tools. The design of substrates based on these technologies offers new possibilities to probe the cellular responses to changes in their physical environment. The investigations of the mechanical interactions of cells and their surrounding matrix can be carried out in well-defined and near physiological conditions. In particular, this includes the transmission of forces as well as rigidity and topography sensing mechanisms. Here, we review techniques and tools based on nano- and micro-fabrication that have been developed to analyze the influence of the mechanical properties of the substrate on cell functions. We also discuss how microfabrication methods have improved our knowledge on cell adhesion and migration and how they could solve remaining problems in the field of mechanobiology. © 2010 International Federation for Medical and Biological Engineering.
CRIS-Team Scopus Importer:2024-02-19
Keywords: Cell contractility; Cell mechanics; Integrins; Mechanotransduction; Microfabrication; Substrate stiffness; Topography